Haikyu!! 14, Quitter's battle - Furudate, Haruichi, 1983- (Shonen Jump manga., 2017)
"It's the middle of the quarterfinal round of the Spring Tournament Qualifiers, and Karasuno's captain, Daichi Sawamura, is injured! With their most reliable player out of the game, the only one who can replace him is...Chikara Ennoshita?!" -- provided by publisher.